Urokinase plasminogen activator receptor is expressed in invasive cells in gastric carcinomas from high- and low-risk countries - Alpízar Alpízar, Warner (2009)
artículo -- Universidad de Costa Rica, Instituto de Investigaciones en Salud. 2009.